The Ethical Principles in Ethical Guidance Documents during the COVID-19 Pandemic in the United Kingdom and the Republic of Ireland: A Qualitative Systematic Review - Hussein, Ghaiath (My University, 2024)
Background: The sudden onset of the coronavirus disease 2019 (COVID-19) pandemic was accompanied by a myriad of ethical issues that prompted the issuing of various ethical guidance documents for health care professionals in clinical, research, and public health settings throughout the United Kingdom (UK) of Great Britain and Northern Ireland and the Republic of Ireland. The aim of this review was to identify the main principles in ethical guidance documents published in the UK and Ireland during the COVID-19 pandemic. Methods: This review used a qualitative systematic review methodology with thematic synthesis to analyze the included ethics-related guidance documents, as defined in this review, published in the UK and Ireland from March 2020 through March 2022. The search included a general search in Google Scholar and a targeted search on the websites of the relevant professional bodies and public health authorities in the two countries. The ethical principles in these documents were analyzed using the constant comparative method (CCM). Results: Forty-four guidance documents met the inclusion and exclusion criteria. Ten main ethical principles were identified, namely: fairness, honesty, minimizing harm, proportionality, responsibility, autonomy, respect, informed decision making, duty of care, and reciprocity. Conclusion: The guidelines did not present the ethical principles in equal detail. Some principles lacked definitions, leaving them vulnerable to misinterpretation by the documents’ end users. Priority was frequently given to collectivist ethics over individualistic approaches. Further clarity is required in future ethical guidance documents to better guide health care professionals in similar situations.
PUBLISHED
Prehospital and Disaster Medicine. Published online 2024:1-11. doi:10.1017/S1049023X24000396
Keywords: ethics; public health; pandemic; COVID-19; Inclusive Society; International Development; MEDICAL EDUCATION; Medical Ethics; Meta-ethics; PUBLIC HEALTH; Public Health ethics; Other